Is dry bulk shipping still worth investing in? - Goh, Cheryl Joy Ying Li (2017)
Fraught with various risks and perils, the volatile dry bulk industry faces a deepening crisis of tepid demand and a surplus of vessels for hire where investors are often susceptible to market exposure and rational behaviour. However, as shipping is often cyclical, it remains to be seen whether the dry bulk industry is still worth investing in during this current depressed market. While past literatures have attempted to understand the trajectory of the dry bulk industry through various methods such as forecasting models, they only consider the quantitative approach through historical data available in the market. In this paper, forecasts shall be attempted in both quantitative and qualitative measures to predict the trajectory of the dry bulk industry in various segments, including the world fleet size and seaborne demand trade. Quantitatively, historical data were collated and put through a time-series based forecasting method to project the future of the dry bulk industry. Qualitatively, the opinions garnered from experienced shipping professionals through interviews were likewise collated to put together a qualitative forecast of the dry bulk industry. The combined results of the forecast could prove valuable for dry bulk investors in crafting appropriate investment strategies in this current depressed market.